(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article is devoted to the famous scientists of the University: A.Kh. Kasymzhanov, K.Kh. Rakhmatullin, M.S. Orynbekov, O.A. Segizbaev, A.Zh. Kelbuganov, B.G. Nurzhanov. In a small essay on the nature of philosophical thinking, inquisitiveness of mind and intellectual courage, some ideas, meanings and themes that were raised in the works of our Kazakh philosophers who taught at the University are discussed.